Multiple-phase carbon-coated FeSn2/Sn nanocomposites for high-frequency microwave absorption. (January 2016) - Zhang, Xuefeng; Rao, Yi; Guo, Junjie; Qin, Gaowu
Abstract: Rapid expansion in microelectronic devices has prompted increasing research efforts in development of high-frequency electromagnetic wave absorption materials. Multiple-phase FeSn2 /Sn/Graphite core–shell nanoparticles synthesized by an arc-discharge method, with controllable components and structures, present a typical cloaking feature aroused from the superior electromagnetic wave absorption. Based on transmission line theory, we prove quantitatively that more than 90% of the electromagnetic power can be attenuated at 9–18 GHz. Experimental results coupled with theory calculations by the Cole–Cole equation and the eddy-current model, further reveal that such high performances are originated from the onion-type interfacial architecture at nanoscale and the desirable impedance match resulting from multiple phase components.